Evidence-Based Strategies to Reduce Postoperative Complications in Plastic Surgery. (September 2016) - Harrison, Bridget; Khansa, Ibrahim; Janis, Jeffrey E.
Abstract : Summary: Reconstructive plastic surgery is vital in assisting patients with reintegration into society after events such as tumor extirpation, trauma, or infection have left them with a deficit of normal tissue. Apart from performing a technically sound operation, the plastic surgeon must stack the odds in the favor of the patient by optimizing them before and after surgery. The surgeon must look beyond the wound, at the entire patient, and apply fundamental principles of patient optimization. This article reviews the evidence behind the principles of patient optimization that are commonly used in reconstructive surgery patients.